Efficiency and effectiveness of road infrastructure - Rokhedi Priyo Santoso; Annirahmah Annirahmah; Florischa Ayu Tresnatri (Universitas Islam Indonesia, 2017)
This study was to analyse the efficiency and effectiveness of provincial road infrastructure performance Yogyakarta Province. The indicators of the efficiency measurement are congestion level, road maintenance, rehabilitation and improvement and the cost. Using the data envelopment analysis method, there was an only one out of fourteen road segment that is fully efficient. On average the efficiency level was quite low that is 34.9 percent due to equally treated system by local government regardless its utilization level. Whereas the effectiveness of road performance is measured by the satisfaction level using indicator of value for time and money, comfort and convenience, safety aspect, travel amenities and road signs. The satisfaction level of road user toward performance of the most efficient road segment is relatively high that is 73.73%.